Genome‐wide associations of leaf spectral variation in MAGIC lines of Nicotiana attenuata - Cheng Li; Ewa A. Czyż; Bernhard Schmid; Rishav Ray; Rayko Halitschke; Ian T. Baldwin; Michael E. Schaepman; Meredith C. Schuman (Ecology, 2026)
The application of in‐field and aerial spectroscopy to assess functional and phylogenetic variation in plants has led to novel ecological insights and supports global assessments of plant biodiversity. Understanding how plant genetic variation influences reflectance spectra will help harness this potential for biodiversity monitoring and improve understanding of why plants differ in functional responses to environmental change. Here, we use a well‐resolved genetic mapping population derived from Multiparent Advanced Generation Inter‐cross (MAGIC) lines of Nicotiana attenuata to associate genetic differences with differences in leaf spectra between plants in a field experiment in their natural environment. We analyzed the leaf reflectance spectra using a hand‐held spectroradiometer (350–2500 nm) on 616 fully genotyped plants of N. attenuata grown in a randomized block design. We tested three approaches to conducting genome‐wide association studies on spectral variants. We introduce a new hierarchical spectral clustering with parallel analysis (HSC‐PA) method. This method efficiently captured the variation in our high‐dimensional dataset and allowed us to discover a novel association, between a locus on chromosome 1 and the 734–1143 nm spectral range, spanning the red‐edge and near‐infrared regions that are sensitive to leaf structure and photosynthetic activity. This locus contains a candidate gene annotated as carbonic anhydrase, an enzyme involved in CO₂ hydration and regulation of photosynthetic efficiency, suggesting a physiological link between variation in leaf optical properties and carbon assimilation. In contrast, an approach treating single wavelengths as phenotypes identified genetic signals highly consistent with HSC‐PA, but suffered from massive statistical redundancy without pinpointing significant, interpretable features. An index‐based approach, which reduces complex spectra to a few dimensionless variables, detected two significant associations for (a water‐content‐related index) with loci on chromosome 1 near genes annotated as a Zeta toxin domain‐containing protein, and an Exocyst subunit Exo70 family protein. While these findings are biologically plausible, they represent a very narrow subset of the spectral variation captured by HSC‐PA. The HSC‐PA approach supports a comprehensive understanding of the genetic determinants of leaf spectral variation that is data‐driven but human‐interpretable and is thus a tool to discover genetic differences underlying intraspecific variation, a foundation of biodiversity.

Carbonyl products of ozone oxidation of volatile organic compounds can modulate olfactory choice behavior in insects - Vignesh Venkateswaran; Ibrahim Alali; Anjana P. Unni; Jerrit Weißflog; Rayko Halitschke; Bill S. Hansson; Markus Knaden (Environmental Pollution, 2023)

Herbivore damage-induced production and specific anti-digestive function of serine and cysteine protease inhibitors in tall goldenrod, Solidago altissima L. (Asteraceae) - Robert F. Bode; Rayko Halitschke; André Kessler (Planta, 2013)

Leaf herbivory increases plant fitness via induced resistance to seed predators - Scott H. McArt; Rayko Halitschke; Juha-Pekka Salminen; Jennifer S. Thaler (Ecology, 2013)
Early‐season herbivory can cause plants to induce resistance to subsequent herbivores, and this ubiquitous plant defense strategy has been shown to be adaptive when subsequent vegetative‐feeding herbivores impact plant fitness. However, a growing number of studies show that leaf herbivory can also induce defenses in plant reproductive tissues, which may deter mutualists such as pollinators and seed dispersers, or antagonists such as florivores and seed predators. Due to their direct interaction with plant reproductive tissues, deterrence of these mutualists or antagonists may have large negative or positive effects on plant fitness. Despite numerous predictions, we know little regarding the fitness consequences of leaf‐to‐reproductive tissue induction in nature. Here, using observations of natural populations and manipulative field experiments, we show that leaf herbivory by the invasive Japanese beetle ( Popillia japonica ) induces an accumulation of jasmonic acid and complex phenolics in reproductive tissues of the common evening primrose ( Oenothera biennis ). Consequently, seed predation by three native Lepidoptera is reduced by 77% on beetle‐induced plants, while leaf herbivory itself has little impact on lifetime reproductive output. These results show that O. biennis benefits from being consumed by an invasive folivore, and that leaf‐to‐reproductive tissue induction can be an adaptive trait. Induced plant defenses can therefore be beneficial in a broader community context than previously realized.

Salicylate‐mediated interactions between pathogens and herbivores - Jennifer S. Thaler; Anurag A. Agrawal; Rayko Halitschke (Ecology, 2010)
Plants employ hormone‐mediated signaling pathways to defend against pathogens and insects. We tested predictions about the relative effect of jasmonate and salicylate pathways and how they mediate interactions between pathogens and herbivores. We employed two pathogens of tomato, Pseudomonas syringae ( Pst ) and tobacco mosaic virus (TMV), that are known to elicit distinct components of the two pathways, and we address the consequences of their induction for resistance in wild‐type and salicylate‐deficient transgenic plants in field experiments. We report that Pst infection induced jasmonic acid and proteinase inhibitors (PIs), and reduced the growth of Spodoptera exigua caterpillars on wild‐type and salicylate‐deficient plants. Pst and TMV both induced salicylic acid in wild‐type but not salicylate‐deficient plants. Although TMV did not affect jasmonic acid or PIs, infection increased caterpillar growth on wild‐type plants, but not on salicylate‐deficient plants. Aphid population growth was higher on salicylate‐deficient compared to wild‐type plants, and lower on salicylate‐induced plants compared to controls. Natural aphid colonization was reduced on TMV‐infected wild types, but not on salicylate‐deficient plants. In sum, jasmonate‐mediated resistance is induced by some pathogens, independent of salicylate, and salicylate‐mediated induction by other pathogens results in induced susceptibility to a chewer and resistance to an aphid. We conclude with a predictive model for the expression of defense pathways and their consequences.

The potato R locus codes for dihydroflavonol 4-reductase - Yongfei Zhang; Shuping Cheng; Darlene De Jong; Helen Griffiths; Rayko Halitschke; Walter De Jong (Theoretical and Applied Genetics, 2009)

Effects of Plant Vascular Architecture on Aboveground–Belowground-Induced Responses to Foliar and Root Herbivores on Nicotiana tabacum - Ian Kaplan; Rayko Halitschke; André Kessler; Sandra Sardanelli; Robert F. Denno (Journal of Chemical Ecology, 2008)

Physiological integration of roots and shoots in plant defense strategies links above‐ and belowground herbivory - Ian Kaplan; Rayko Halitschke; Andre Kessler; Brian J. Rehill; Sandra Sardanelli; Robert F. Denno (Ecology Letters, 2008)
Roots play a critical, but largely unappreciated, role in aboveground anti‐herbivore plant defense (e.g. resistance and tolerance) and root–leaf connections may therefore result in unexpected coupling between above‐ and belowground consumers. Using the tobacco ( Nicotiana tabacum ) system we highlight two examples of this phenomenon. First, the secondary metabolite nicotine is produced in roots, yet translocated aboveground for use as a foliar resistance trait. We demonstrate that nematode root herbivory interferes with foliar nicotine dynamics, resulting in positive effects on aboveground phytophagous insects. Notably, nematode‐induced facilitation only occurred on nicotine‐producing plants, and not on nicotine‐deficient mutants. In the second case, we use stable isotope and invertase enzyme analyses to demonstrate that foliar herbivory elicits a putative tolerance response whereby aboveground nutritional reserves are allocated to roots, resulting in facilitation of phytoparasitic nematodes. Thus, plants integrate roots in resistance and tolerance mechanisms for leaf defense, and such root–leaf connections inherently link the dynamics of above‐ and belowground consumers.

Shared signals –‘alarm calls’ from plants increase apparency to herbivores and their enemies in nature - Rayko Halitschke; Johan A. Stenberg; Danny Kessler; André Kessler; Ian T. Baldwin (Ecology Letters, 2008)
The attraction of natural enemies of herbivores by volatile organic compounds as an induced indirect defence has been studied in several plant systems. The evidence for their defensive function originates mainly from laboratory studies with trained parasitoids and predators; the defensive function of these emissions for plants in natural settings has been rarely demonstrated. In native populations and laboratory Y‐tube choice experiments with transgenic Nicotiana attenuata plants unable to release particular volatiles, we demonstrate that predatory bugs use terpenoids and green leaf volatiles (GLVs) to locate their prey on herbivore‐attacked plants. By attracting predators with volatile signals, this native plant reduces its herbivore load – demonstrating the defensive function of herbivore‐induced volatile emissions. However, plants producing GLVs are also damaged more by flea beetles. The implications of these conflicting ecological effects for the evolution of induced volatile emissions and for the development of sustainable agricultural practices are discussed.

Independently silencing two JAR family members impairs levels of trypsin proteinase inhibitors but not nicotine - Lei Wang; Rayko Halitschke; Jin-Ho Kang; Albrecht Berg; Falk Harnisch; Ian T. Baldwin (Planta, 2007)

Priming of plant defense responses in nature by airborne signaling between Artemisia tridentata and Nicotiana attenuata - André Kessler; Rayko Halitschke; Celia Diezel; Ian T. Baldwin (Oecologia, 2006)

Jasmonates and related compounds in plant-insect interactions - Rayko Halitschke; Ian T. Baldwin (Journal of Plant Growth Regulation, 2004)

Jasmonates and Related Compounds in Plant-Insect Interactions - Rayko Halitschke; Ian T. Baldwin (Journal of Plant Growth Regulation, 2004)

Individual variability in herbivore‐specific elicitors from the plant's perspective - AMY RODA; RAYKO HALITSCHKE; ANKE STEPPUHN; IAN T. BALDWIN (Molecular Ecology, 2004)
Lepidopteran larvae oral secretions and regurgitant (R), which contain a plethora of potential elicitors, are known to dramatically change a plant's wound response. We demonstrate, with a detailed microarray and secondary metabolite analysis, that the two most abundant fatty acid‐amino acid conjugates (FACs) in the R of the specialist herbivore Manduca sexta (Lepidoptera, Sphingidae) can account for all measured direct (trypsin proteinase inhibitor: TPI) and indirect ( cis ‐α‐bergamotene) defences, the endogenous jasmonic acid burst that elicits them, and 86% of the induced transcriptional changes (89% up and 83% down) in its native host Nicotiana attenuata and hence are necessary and sufficient for the Manduca ‐specific modulation of the wound response. FACs were not found in eggs, but detected in larvae of all instars after their first meal. FACs were found in all regions of the alimentary canal and in the frass, but did not occur in salivary or mandibular glands, extracts of which were not active in any assay. Individual larvae differed substantially in their FAC composition and two FAC chemotypes were discernible: N ‐linolenoyl‐L‐glutamine biased R and N ‐linolenoyl‐L‐glutamate biased R. We created synthetic blends of FACs to mimic these chemical phenotypes and determined whether plants respond differently to the different R chemotypes. Micorarray and TPI analysis revealed that plants do not differentiate. N. attenuata plants use FACs from feeding caterpillars to tailor their wound responses but do not use the variability in FAC ratios to recognize attack from an individual caterpillar.